Presence II - Robert Andrew (2021)
Yawuru descendent Robert Andrew’s artwork Presence II was featured in Dhagun at La Boite for their program Block Party. Dhagun is a yearlong outdoor exhibition integrating First Nations voices responding to Country. Dhagun is a yuggera language word meaning earth, place or country. This exhibition series was curated by Blaklash. Presence II is a video artwork that overlays mineral and pigment details from Andrew’s installations to visualise his evolving relationship to Country. This artwork was presented as a large-scale projection on the side of the La Boite building.